Youtube As A Learning Medium (Communication Student Perceptions of Using Youtube Channels as an Alternative Medium of Learning in the Digital Age) - Haryo Kusumo Aji dan Fanny Hendro Aryo Putro (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Learning in the digital Age must follow the development of the era, no longer haveto face to face in the classroom but can be done anywhere and can be accessedusing a device. Youtube as a video-based online media can be a good alternativefor young people to learn and deepen everything that is not obtained in theclassroom. This study focuses on the perception of students in using youtubechannel in the major of Communication Studies program, because the subject oflearning in this Department is very dynamic and must follow the development ofthe era.This research method is qualitative with in-depth interviews to students who studyCommunication Science and see youtube channel that focuses on teaching certaintechniques in communication science.The result of the research shows that the student motive in using youtube becauseof the lack of real practice example in the course material and to add insight. Thenthe external factor that makes someone use youtube to learn is because it is easyand interesting to be accessed and can be shared by others through the sharefeature.Then for the value embraced by the students is a change of view from youtube thatoriginally used for entertainment becomes a place to find materials learning morecomplete and detailed and there are special tricks of certain materials. From theside of the culture adopted, majority students come from the Indonesian nation,therefore more follow the channel that uses Indonesian language more easilyunderstood. The hope is that more and more informative content from localuploaded on youtube so that learning can be obtained by all people and specificallythe Indonesian nation without limitation of distance and time.Keyword: Youtube Channel; Alternative Medium; Digital Age; Perception; Learning Medium